Ion Dynamics in Single and Multi-Cation Perovskite. (6th August 2020) - Shikoh, Ali Sehpar; Polyakov, A. Y.; Smirnov, N. B.; Shchemerov, I. V.; Saranin, D. S.; Didenko, S. I.; Kuznetsov, D. V.; Agresti, A.; Pescetelli, S.; Di Carlo, A.
Abstract : In organic-inorganic perovskites currently widely used to fabricate high-efficiency solar cells the electrical properties are to a large extent determined by the presence of mobile ions. These mobile ions are commonly held responsible for many undesirable features of perovskite solar cells, such as hysteretic behavior of electrical properties and degradation of parameters during operation. Hence, developing methods to study the properties of mobile ions and distinguish their contribution to electrical properties from the usual effects due to electronic states are essential for gaining control over the type and density of mobile ions. In this paper we show that comparison of deep levels transient spectroscopy (DLTS) measurements performed in the normal and reverse biasing/pulsing sequences provides a useful means of discriminating between the contributions of electronic traps usual for all semiconductors and the mobile ions very important in perovskites. To simplify things these experiments were performed on Schottky diodes rather than heterojunctions with organic-inorganic electron transport and hole transport layers. The results of experiments are presented and compared for single cation MAPbI3 and multication perovskites. In both cases the main features observed in DLTS could be attributed to mobile ions.